Leadership capabilities of physiotherapy leaders in Ireland: Part 1 physiotherapy managers. - McGowan, Emer; Elliott, Naomi; Stokes, Emma (Physiotherapy Theory & Practice, 2019)
Background: Investigation of the leadership capabilities of physiotherapists is needed to allow understanding of current leadership practice and to enable appropriate training programs to be developed. Purpose: To explore physiotherapy managers´ perceptions of their leadership capabilities. Methods: Semi-structured interviews were conducted with a purposive sample of 18 physiotherapy managers from a range of public services and private practices in Ireland. The interviews were analyzed using template analysis and the coding template was based on the Bolman and Deal Leadership framework which details four leadership frames: structural, human resource, political, and symbolic. Results: The physiotherapy managers described demonstrating leadership capabilities associated with each of the four leadership frames. However, the language used by the physiotherapy managers suggested that they work predominantly through the structural and human resource frames. The employment of capabilities associated with the political frame varied between participants; some participants described working through this frame while others reported difficulties. The symbolic frame was underused; there were fewer examples given of capabilities such as communicating their vision, demonstrating passion and facilitating a positive workplace culture. Conclusions: Physiotherapy managers work predominantly through the structural and human resource frames. To successfully meet the leadership requirements of their roles physiotherapy managers may benefit from specific leadership development training to develop leadership capabilities in the political and symbolic frames.